Implementation of DSN-MUI Fatwa In Handling of Sharia Economic Problems (A Case In Syariah Bank of Bandar Lampung) - Tahmid, Khairuddin; Zaki, Muhammad; H, Haryanto (al-'adalah, 2019)
This study aims to reveal the position of the fatwa of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) in the national legal system as well as to learn how it is applied in the Bandar Lampung People's Credit Bank (BPRS) Bandar Lampung. The DSN-MUI fatwa was issued to avoid the different provisions made by the Sharia Supervisory Board (DPS) in each Islamic financial institution. With the DSN MUI fatwa, the provisions for all sharia economic actors will be the same so as to create legal order. This research found that the DSN MUI fatwa was not fully implemented in the activities carried out by the Bank. Where as, in the national legal system, the DSN MUI fatwa is considered as part of positive law and has become a law in concreto for judges and arbitrators in Basyarnas. Therefore it is imperative that all sharia financial institutions to fully implement all the existing provisions, not just in part.